Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1969
DOI: 10.1084/jem.129.2.431
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Interaction in the Development of Thymus Lymphocytes

Abstract: Thymic rudiments from chick and mouse embryos have been cultured in diffusion chambers on the chick chorioallantois. In this situation their supply of blood-borne stem cells is cut off. Although rudiments from older embryos become fully lymphoid under these circumstances, primordia from early embryos fail to develop any lymphoid cells. Early chick rudiments will however develop completely if they are grafted directly to the chorioallantois where they receive a vascular supply. It is concluded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
5

Year Published

1972
1972
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(98 citation statements)
references
References 19 publications
4
89
0
5
Order By: Relevance
“…One is the rat T cell population that was present in the thymic grafts and migrated into peripheral lymphoid tissues, while the other is mouse T cell population educated in the grafts . In the mouse, it is reported that lymphoid precursor cells first enter the fetal thymus at 10 .5 d of gestation (3) . The developmental stage of rat thymus is almost the same as that of mouse, or slightly behind.…”
Section: Resultsmentioning
confidence: 99%
“…One is the rat T cell population that was present in the thymic grafts and migrated into peripheral lymphoid tissues, while the other is mouse T cell population educated in the grafts . In the mouse, it is reported that lymphoid precursor cells first enter the fetal thymus at 10 .5 d of gestation (3) . The developmental stage of rat thymus is almost the same as that of mouse, or slightly behind.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of Spatial in 10 day embryos slightly precedes the budding of the thymus and its initial seeding by HSC at about day 10.5 to day 11. 16,17,26 The timing of embryonic Spatial expression is coincident with the HSC seeding of the fetal liver from the yolk sac and para-aortic splanchnopleura which starts at around day 10, peaks at day 13 and then declines. 27,28 In fact, RT-PCR analysis of fetal tissues revealed that Spatial is also expressed in the 14 day fetal liver, but not in adult liver (Figure 6a).…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stem cell (HSC) seeding of the thymus begins at embryonic day 10 when waves of cells colonize the thymic rudiment while it is still attached to the pharyngeal pouch. [15][16][17] The products that attract HSC to the thymus are unknown but recent experiments have indicated that chemokines, integrins, and CD44 mediate the seeding of the thymus by HSC. [18][19][20] Upon entry into the thymus, HSC start to differentiate and the resulting daughter cells divide multiple times to a point where 95% of the thymus is composed of a transient population of lymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…The thymus rudiment is devoid of lympho-hematopoietic potentiality until ~E10.5 when an influx of progenitors begins (Owen and Ritter, 1969). GFP + cells, which were actually the first ones during embryonic development, became conspicuous both within and surrounding the thymus rudiment slightly later (Fig.…”
Section: Initiation Of Lymphopoiesis In the Fetal Thymusmentioning
confidence: 99%